USE OF CLOUD COMPUTING FOR DEVELOPMENT OF TEACHERS’ INFORMATION AND COMMUNICATION COMPETENCE - Soroko, N.; Shinenko, M. (Journal of Information Technologies in Education (ITE), 2014)
The article deals with the problem for development of techers’ information and communication competence and use of cloud computing for it. The analysis of the modern approaches to the use of cloud technologies and projects for professional development of teachers and development of teachers’ information and communication competence have been presented.There are the main characteristics of software as a service on the Internet for education leading companies Google, Microsoft, IBM. There are described some actions of these companies,which are conducted to help teachers to master cloud technology for improving the professional activities and development of teachers’ information and communication competence. The examples of ways of development of teachers’ information and communication competence and training teachers to use modern ICT in the professional activity are given in the paper. The Cloud based model for development of teachers’ information and communication competence has been proposed.